Morphology of the Musculus Uvulae In Vivo Using MRI and 3D Modeling Among Adults With Normal Anatomy and Preliminary Comparisons to Cleft Palate Anatomy. - Perry, Jamie L.; Chen, Joshua Y.; Kotlarek, Katelyn J.; Haenssler, Abigail; Sutton, Bradley P.; Kuehn, David P.; Sitzman, Thomas J.; Fang, Xiangming (Cleft Palate Craniofacial Journal, 2019)
Purpose: To investigate the musculus uvulae morphology in vivo in adults with normal velopharyngeal anatomy and to examine sex and race effects on the muscle morphology. We also sought to provide a preliminary comparison of musculus uvulae morphology in adults with normal velopharyngeal anatomy to adults with repaired cleft palate. Methods: Three-dimensional magnetic resonance imaging data and Amira 5.5 Visualization Modeling software were used to evaluate the musculus uvulae in 70 participants without cleft palate and 6 participants with cleft palate. Muscle length, thickness, width, and volume were compared among participant groups. Results: Analysis of covariance analysis did not yield statistically significant differences in musculus uvulae length, thickness, width, or volume by race or sex among participants without cleft palate when the effect of body size was accounted for. Two-sample t test revealed that the musculus uvulae in participants with repaired cleft palate is significantly shorter (P =.008, 13.65 mm vs 16.07 mm) and has less volume (P =.002, 51.08 mm3 vs 97.62 mm3) than participants without cleft palate. Conclusion: In adults with normal velopharyngeal anatomy, the musculus uvulae is a cylindrical oblong-shaped muscle lying on the nasal surface of the soft palate, with its greatest bulk located just nasal to the levator veli palatini muscle sling. In participants with repaired cleft palate, the musculus uvulae is substantially reduced in volume. This diminished muscle bulk located just at the point where the palate contacts the posterior pharyngeal wall may contribute to velopharyngeal insufficiency in children with repaired cleft palate.